Experimental Investigations on Hybrid Vehicle - G. Mohammed, Khalid; ., .; ., . (International Journal of Engineering and Technology, 2018)
Electric driving is one of the main courses in energy science. It represents the relationship between an electric motor as a tool to convert electrical energy into mechanical energy and between a managed or mechanical device that drives it through belts or gears. In the current research, a three-phase synchronous motor 1200 Watt was used to drag an electric vehicle with a rated load of 150 kg and at a speed of up to 40 km per hour. Transmission from the electric motor to the vehicle's tires is done through a gear to rotate the wheels of the vehicle. Batteries are used to store continuous electrical power from a 220-volt alternating power source using the DC/AC inverter. Solar energy 150 Watt has also been used by using a solar panel placed on the roof of the vehicle. Mechanical energy has also been used by mechanical pedal. The vehicle was tested on a flat and sloping road in Baquba / Diyala province / Iraq. The efficiency tests proved the acceleration and balance of the car are good and matched with the theoretical calculations.Â Â Â